Help-seeking behaviours among older adults: a scoping review protocol. Issue 2 (16th February 2021) - Teo, Kelly; Churchill, Ryan; Riadi, Indira; Kervin, Lucy; Cosco, Theodore
Abstract : Introduction: Despite evidence that illustrates the unmet healthcare needs of older adults, there is limited research examining their help-seeking behaviour, of which direct intervention can improve patient outcomes. Research in this area conducted with a focus on ethnic minority older adults is also needed, as their help-seeking behaviours may be influenced by various cultural factors. This scoping review aims to explore the global literature on the factors associated with help-seeking behaviours of older adults and how cultural values and backgrounds may impact ethnic minority older adults' help-seeking behaviours in different ways. Methods and analysis: The scoping review process will be guided by the methodology framework of Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols Extension for Scoping Reviews guidelines. The following electronic databases will be systematically searched from January 2005 onwards: MEDLINE/PubMed, Web of Science, PsycINFO, CINAHL and Scopus. Studies of various designs and methodologies consisting of older adults aged 65 years or older, who are exhibiting help-seeking behaviours for the purpose of remedying a physical or mental health challenge, will be considered for inclusion. Two reviewers will screen full texts and chart data. The results of this scoping review will be summarised quantitatively through numerical counts and qualitatively through a narrative synthesis. Ethics and dissemination: As this is a scoping review of published literature, ethics approval is not required. Results will be disseminated through publication in a peer-reviewed journal. Discussion: This scoping review will synthesise the current literature related to the help-seeking behaviours of older adults and ethnic minority older adults. It will identify current gaps in research and potential ways to move forward in developing or implementing strategies that support the various health needs of the diverse older adult population. Registration: This scoping review protocol has been registered with the Open Science Framework (https://osf.io/69kmx ).